Adiksi Internet pada Remaja - Prambayu, Ismalia; Dewi, Mulia Sari (TAZKIYA Journal of Psychology, 2019)
Internet addiction has become a worrying phenomenon for Indonesian teenagers. This research was conducted to determine whether the psychological factors will influence internet addiction in adolescents. This research uses quantitative with multiple regression analysis method. The winning sample is 200 adolescents. The instrument collects data using a scale internet addiction scale that compiled by Griffiths (2005) and developed by Lemmens (2009), Parenting Authority Questionnaire (PAQ) developed by Buri (1991), Social Skill Inventory (SSI) developed by Riggio (1986), and A Rasch-Type Loneliness Scale compiled by De Jong Gierveld (2006).  The results showed that there were significant differences in the parenting style, social skills, and loneliness on the tendency of internet addiction in adolescents.